Analisis Motivasi Belajar House Keeping Praktek Terhadap Prestasi Belajar Mahasiswa Sekolah Tinggi Pariwisata Trisakti - Darsiah, Anis (Jurnal Ilmiah Pariwisata; Vol 24 No 1 (2019): Jurnal Ilmiah PariwisataDO - 10.30647/jip.v24i1.1240, 2019)
This study purpose to find how big relationship between motivation to study house keeping part II practices toward student’s learning achievement at the fourth semester of Tourism Institute in Trisakti. It can improve knowledge and finding that individual study motivation will become the result of studying achievement has increased, while Tourism Institute in Trisakti especially for coordinator  and  lecturer of  housekeeping  discipline.  This  report  can  be  used  as  input  or consideration support on improving student’s motivation to study housekeeping part II and finding the way which can be applied to enhance or improve student’s studying achievement. Research  method  used  a  descriptive  method  and  correlation  to  find  how  big  relationship between  studying  motivation  toward  studying  achievement.  Collecting  primary  data  used observation method where the questionnaires were distributed to students, while the secondary data were obtained from the various library materials. This study concluded that studying motivation will effect to studying achievement and having relationship of medium correlation that  was  0.52.  Studying  motivation  effected  27.04%  of  student’s  studying  achievement, especially for discipline of housekeeping part II practices at Tourism Institute in Trisakti, while the remains of 72.96% were effected by another factors which were not examined at the end of this project